A century of fishery data documenting the collapse of smooth‐hounds (Mustelus spp.) in the Mediterranean Sea - Colloca, Francesco; Enea, Marco; Ragonese, Sergio; Di Lorenzo, Manfredi (Aquatic conservation, 2017)
Conservation and management of shark populations is increasingly becoming important in many marine regions, since there is a growing body of evidence showing that several species are threatened and continuing to decline because of unregulated fishing. Quantifying the extent of sharks' decline, the risk of species extinction, and the consequences for marine ecosystems have been challenging and controversial, mostly due to data limitations. In this study, more than one century of multiple‐sources of bibliographic records on presence and frequency of occurrence of three species of commercial sharks, the smooth‐hounds Mustelus spp., in the Mediterranean Sea were compiled and analysed. Generalized additive models for location, scale and shape (GAMLSS) were used to estimate the rate of change of two of these species, Mustelus mustelus and Mustelus punctulatus, in four Mediterranean regions. Model results showed that smooth‐hounds have declined by 80–90% since the beginning of last century to almost disappear in a large part of their original distributional range during the 1980s and 1990s. Based on modelling results, a revision of the current International Union for Conservation of Nature classification of Mediterranean smooth‐hounds would be advisable along with the application of urgent conservation measures.